Analisis Jalur Trans Kutaraja di Kota Banda Aceh di Tinjau Dari Pengembangan Wilayah - Renny Anggeraeni Robin; Noer Fadhly; Ashfa Achmad (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2021)
ABSTRACT Banda Aceh City is the capital of Aceh Province with a population growth rate of 1.97%, has a city spatial planning area of 6,136 Ha, or 5,903 Ha based on digitizing Satellite Imagery, with a population in 2019 of 270,321 thousand people, and a density population of 4,405 people/ km2 . Trans Kutaraja is one mode of transport public road based in the city of Banda Aceh has been in operation since 2016. Banda Aceh with all aktivistas in it continues to develop, the land use pattern is dominated by residential areas of 52.62%, trade and services areas of 13.38%, public service areas of 6.30%, office areas of 2.37% and mixed areas of 2.79%. Population density can affect accessibility in achieving travel destinations , increasing travel will lead to the need for transportation facilities , currently the percentage of Trans Kutaraja service coverage still has not reached all corners of the city of Banda Aceh, which is 31%. Keywords: Public Transportation, Accessibility, Banda Aceh City.